Ultrafine molybdenum oxycarbide nanodots encapsulated in N, P co-doped carbon nanofibers as an advanced anode material for lithium-ion batteries. (30th April 2021) - Li, Huanhuan; Sun, Huayang; Wang, Kui; Wang, Yaping; Wang, Nan; Lv, Xiaoxin; Jiang, Haobin; Chen, Long
Abstract: Molybdenum oxycarbide (MoOC) is a single-phase compound, which can serve as a potential anode for Li-ion batteries (LIBs) that integrates the merits of the high specific capacity of MoO2 and high conductivity of Mo2 C. Herein, a novel architecture with N, P co-doped C nanofibers and MoOC nanodots is constructed from a one-step phosphorization of MoO x /aniline organic–inorganic hybrid. Ultrafine MoOC nanodots are well confined by N, P co-doped C nanofibers, which ensures fast Li + /electron transfer and good stability of the structure under repeated charge/discharge processes. When this unique hybrid is employed as an anode material for LIBs, promising Li + storage properties are gained in terms of high specific capacity, superb rate and long-term cycling performance. The remarkable capacitive contribution facilitates the fast Li + uptake/release. This work may shed light on the development of well-defined Mo-based anodes for advanced LIBs.